Effectiveness of Technology Assisted Pronunciation Training Devices for ESOL Learners - Anolin, Camille (JELP Journal of English Language and Pedagogy, 2025)
Technology Assisted Language Learning (TALL) has been a major focus in English education research for decades with a large number of devices and applications being utilized to promote general English proficiency along with targeting specific skills like reading, writing, listening, and speaking. This study investigates uses of TALL in English language classrooms, specifically TALL related to pronunciation training in the form of Technology Assisted Pronunciation Training (TAPT). This paper reviews research on TAPT in English language classrooms, evaluating the effectiveness of commonly used tools in enhancing language learning outcomes. Potential TAPT articles were identified through the search databases of the EBSCO and ProQuest with the key terms such as TAPT, TALL, Computer Assisted Pronunciation Training (CAPT), Mobile Assisted Pronunciation Training (MAPT), English for Speakers of Other Languages (ESOL), and pronunciation training. This review analyzes 10 empirical studies published between 2014 and 2024, encompassing a total of over 1,000 participants, to evaluate the impact of technology-assisted tools on pronunciation, intelligibility, and perception in English language learning. The review findings show that all studies consistently report positiveresults regarding the effectiveness of TAPT devices in enhancing intelligibility, suggesting their potential to significantly improve L2 English learners’ experience in English classrooms.